Inducing competition: intensive grassland seeding to control Ambrosia artemisiifolia. (27th February 2015) - Gentili, R; Gilardelli, F; Ciappetta, S; Ghiani, A; Citterio, S; Zwerger, Peter
Summary The invasion of Ambrosia artemisiifolia across European countries has been favoured by its ecological amplitude and by its ability to colonise and dominate disturbed/ruderal areas that have lost competition from native species. We supposed that a strong competition for habitat resources may inhibit A. artemisiifolia growth, generating a negative feedback to its establishment. Based on this hypothesis, in this study, we undertook a 1‐year field experiment to assess the effect of mixtures of grassland species on A. artemisiifolia growth and fitness in bare soils. We applied three different treatments within an abandoned quarry area invaded by A. artemisiifolia: (i) spontaneous succession, (ii) hayseed and (iii) a commercial seed mixture. Within plots, we recorded vegetation parameters, A. artemisiifolia abundance and traits. Results obtained after one growing season showed that the commercial seed resulted in the strongest reduction of A. artemisiifolia growth rate in terms of plant height, lateral spread and leaf size. This was ascribed to higher density of plants that play a key role in reducing biomass and fitness of A. artemisiifolia. However, hayseed should be preferred, as it preserves local biodiversity. Seeding mixtures of grassland species can successfully suppress A. artemisiifolia in the first year of establishment on a vegetation‐free soil derived from quarry activities. This study indicated that inducing dominance of different native species in a newly developing plant community should enhance competition for resources, reducing the success of early coloniser non‐native species.